Effects of Progressive Gaze Stability Exercises on Balance and Gait in Vestibular Neuritis Patients: A Quasi-experimental Study - Priya Chauhan; SD Shahanawaz; Gaurav Kapoor (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Gaze stability exercises are the exercises that are used effectively to improve gaze stability during head movement in various vestibular disorders patients, and to improve balance in static and dynamic movements of the same. Aim: To compare the effectiveness of progressive gaze stability exercises to improve balance and gait in patients with vestibular neuritis. Materials and Methods: This quasi-experimental study was conducted at Outpatient Department of SGT hospital, Gurugram, Haryana, India, from November 2018 to March 2019. A total of 26 subjects were randomly assigned into two groups, group A received progressive gaze stability exercises with conventional therapy (n=13) and group B received conventional therapy (n=13). Group A received Vestibular Rehabilitation Therapy (VRT) for 25 minutes a day five times a week for four weeks. group B conventional training which consisted of balance exercises. Participants were assessed with Mini Balance Evaluation Systems Test (Mini-BESTest) and dizziness handicap inventory to access the performance of balance and functional limitation, respectively. Data was analysed by using the Statistical Package for the Social Sciences (SPSS) version 20.0 for statistical analysis. A level of significance was set at p-value <0.05. Results: The finding of the study showed no significant change for baseline parameters between the experimental and conventional groups with respect to age (p-value=0.097), gender (p-value=0.573), height (p-value=0.682), weight (p-value=0.945), duration of illness (p-value=0.579). Both the groups showed significant improvement with in group, when measured using dependent t-test for Mini-BESTest and Wisconsin Gait Scale. The comparison of postintervention scores of Mini-BESTest and WGS between group A and group B showed significant difference (p-value=0.001) and (p-value=0.002) respectively. Conclusion: The present study has provided preliminary evidence that progressive gaze stability exercises when coupled with conventional balance exercises may improve gait and balance in patients with vestibular neuritis.